STRUCTURAL ASPECTS OF CHEMISTRY PALLADIUM AND PLATINUM - Angulo Cornejo, Jorge R. (2003)
The chemistry of platinum and palladium is a well studied field and many applications because these metals can form bonds with many organic and inorgánicas molecules. These links are sometimes very reactive, and open countryside to both homogeneous and heterogeneous catalysis. The square planar complexes with oxidation states (II) dominate the coordination chemistry of Pd and Pt This article reviews recent complexes have been synthesized and structurally characterized in the last ten years.